A Fast Multi-Locus Ridge Regression Algorithm for High-Dimensional Genome-Wide Association Studies - Zhang, Jin; Chen, Min; Wen, Yangjun; Zhang, Yin; Lu, Yunan; Wang, Shengmeng; Chen, Juncong (Frontiers in Genetics, 2021)
The mixed linear model (MLM) has been widely used in genome-wide association studies (GWAS) to dissect quantitative traits in human, animal and plant genetics in genomic sequencing technologies. Most methodologies consider all single nucleotide polymorphism (SNP) effects as random effects under the MLM framework, which fail to detect the joint minor effect of multiple genetic markers on a trait. Therefore, polygenes with minor effects remain largely unexplored in today's big data era. In this study, we developed a new algorithm under the MLM framework, which is called the fast multi-locus ridge regression (FastRR) algorithm. The FastRR algorithm first whitens the covariance matrix of the polygenic matrix K and environmental noise, then selects potentially related SNPs among large scale markers, which have a high correlation with the target trait, and finally analyzes the subset variables using a multi-locus deshrinking ridge regression for true quantitative trait nucleotide (QTN) detection. Results from the analyses of both simulated and real data show that the FastRR algorithm is more powerful for both large and small QTN detection, more accurate in QTN effect estimation, and has more stable results under various polygenic backgrounds. Moreover, compared with existing methods, the FastRR algorithm has the advantage of high computing speed. In conclusion, the FastRR algorithm provides an alternative algorithm for multi-locus GWAS in high dimensional genomic datasets.